Induced pluripotent stem cells and personalized medicine: current progress and future perspectives - Chun, Yong Soon; Byun, Kyunghee; Lee, Bonghee (Anatomy & cell biology, 2011)
Generation of induced pluripotent stem cells (iPSCs) has revolutionized the field of regenerative medicine by providing researchers with a unique tool to derive disease-specific stem cells for study. iPSCs can self-renew and can differentiate into many cell types, offering a potentially unlimited source of cells for targeted differentiation into somatic effector cells. Hence, iPSCs are likely to be invaluable for therapeutic applications and disease-related research. In this review, we summarize the recent progress of iPSC generation that has been made with an emphasis on both basic and clinical applications including disease modeling, drug toxicity screening/drug discovery and cell replacement therapy.